'Reading and writing the world' with mathematics in a Middle Eastern context. Issue 2 (1st December 2015) - Tanko, Mohammed Goma
Abstract : Very little work has been published on teaching for social justice in the Middle East. This paper demonstrates how a group of Arab women's reading and writing of their world was facilitated by using a social justice pedagogy based on Gutstein's (2006) model. The study involved 20 Middle Eastern women (ages ranging from 16-36). The findings suggest that the students have developed significant abilities to use mathematics as a tool to read and write their world. In addition, the findings show that, like their counterparts elsewhere in the world, these young women are also interested in social justice issues. This is particularly significant because of current ongoing social developments in the Middle East.